Placenta previa percreta sin diagnóstico antenatal - Valladares Gutiérrez, Elías Alexis (2026)
The spectrum of placenta accreta and in particular placenta previa percreta is an important cause of obstetric hemorrhage and severe maternal and perinatal morbidity and mortality, even in countries and institutions with experience and adequate support. We present the case of a pregnant woman of 34 weeks 2 days, with a history of cesarean section and placenta previa, with an intraoperative diagnosis of percreta who underwent emergency cesarean hysterectomy. Management was complex but successful and without complications. The importance of having the necessary skills to manage placenta previa percreta without antenatal diagnosis is highlighted.